Tuberculosis Detection and the Challenges of Integrated Care in Rural China : A Cross-Sectional Standardized Patient Study - Sylvia, Sean; Xue, Hao; Zhou, Chengchao; Shi, Yaojiang; Yi, Hongmei; Zhou, Huan; Rozelle, Scott; Pai, Madhukar; Das, Jishnu (PLoS, 2018)
Despite recent reductions in prevalence, China still faces a substantial tuberculosis (TB) burden, with future progress dependent on the ability of rural providers to appropriately detect and refer TB patients for further care. This study (a) provides a baseline assessment of the ability of rural providers to correctly manage presumptive TB cases; (b) measures the gap between provider knowledge and practice and; (c) evaluates how ongoing reforms of China’s health system—characterized by a movement toward “integrated care” and promotion of initial contact with grassroots providers—will affect the care of TB patients.